Drug-induced Anaphylaxis - Labella, Marina; de Santa María, Rocío Saénz; Bogas, Gádor; Salas, María; Fernández, Tahía D.; Mayorga, Cristobalina; Torres, Maria José; Doña, Inmaculada (Current Pharmaceutical Design, 2023)
Drug hypersensitivity is increasing worldwide as the consumption of drug is increasing. Many clinical presentations of drug hypersensitivity are complex and take place in the setting of illness and/or polypharmacotherapy. To review the most recent findings in the diagnosis and management of immediate drug hypersensitivity reactions. Studies were selected based on their relevance, originality and date of publication. The understanding of endotypes, biomarkers and phenotypes has improved the categorization of immediate hypersensitivity reactions. In this review, we discussed the short- and long-term management of anaphylaxis with a special focus on in vivo and in vitro diagnostic methods. Moreover, the clinical management of drug-induced anaphylaxis, the role of hidden allergens and the importance of delabeling are discussed. Endophenotyping is crucial to correctly diagnose and treat patients with immediate drug hypersensitivity reactions, preventing future episodes through drug desensitization.
Keywords: desensitization